Respuestas

2012-06-23T07:04:47+02:00

x: menor numero   ;   y: mayor numero       ; y=x+1

 

x^{2} + (y)^{2} = (y) + 10(x+y) 

x^{2} + (x+1)^{2} = (x+1) + 10((x)+(x+1))

x^{2}+x^{2}+2x+1=x+1+10(2x+1)

2x^{2}+2x+1=x+1+20x+10

2x^{2}+2x+1=21x+11

x^{2}+2x+1-21x-11=0

x^{2}-19x-10=0   ;  por aspa simple

(2x+1)(x-10)=0

sacamos que

x={-1/2; + 10}      ;   x pertenece a los enteros

entonces x=10

respuesta: 10 y 11

 

2012-06-23T07:14:23+02:00

comensemos:

 

numero 1: x   numero 2: x+1

 

x^2+(x+1)^2 = x+1+10(x+x+1)

 

x^2+x^2+2x+1 = x+1+20x+10

 

2x^2 +2x+1= 21x +11

 

2x^2 +2x+1-21x-11=0

 

2x^2 - 19x -10

  2x             1

   x            -10

 

(2x+1)(x-10)=0

 

2x+1=0    x-10=0

x=-1/2     x=10

 

por tanto:

 

numero 1 : x = 10

 

numero 2 : x+1 = 10+1 = 11

 

un gusto.....=D